Ionic Covalent Organic Frameworks for Energy Devices. Issue 52 (8th October 2021) - Liang, Xiaoguang; Tian, Ye; Yuan, Yufei; Kim, Yoonseob
Abstract: Covalent organic frameworks (COFs) are a class of porous crystalline materials whose facile preparation, functionality, and modularity have led to their becoming powerful platforms for the development of molecular devices in many fields of (bio)engineering, such as energy storage, environmental remediation, drug delivery, and catalysis. In particular, ionic COFs (iCOFs) are highly useful for constructing energy devices, as their ionic functional groups can transport ions efficiently, and the nonlabile and highly ordered all‐covalent pore structures of their backbones provide ideal pathways for long‐term ionic transport under harsh electrochemical conditions. Here, current research progress on the use of iCOFs for energy devices, specifically lithium‐based batteries and fuel cells, is reviewed in terms of iCOF backbone‐design strategies, synthetic approaches, properties, engineering techniques, and applications. iCOFs are categorized as anionic COFs or cationic COFs, and how each of these types of iCOFs transport lithium ions, protons, or hydroxides is illustrated. Finally, the current challenges to and future opportunities for the utilization of iCOFs in energy devices are described. This review will therefore serve as a useful reference on state‐of‐the‐art iCOF design and application strategies focusing on energy devices. Abstract : Ionic covalent organic frameworks (iCOFs) are porous crystalline polymeric materials where the backbone is composed of 100% covalent bonds and on which ionic groups are functionalized. iCOFs can transport ions rapidly and reliably through the pores. Thus, they are ideal materials for solid electrolytes. Examples prove iCOFs show excellent performance to make all‐solid‐state and single‐ion‐conducting Li‐ion batteries.